2018
DOI: 10.1016/j.omtn.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

circGprc5a Promoted Bladder Oncogenesis and Metastasis through Gprc5a-Targeting Peptide

Abstract: Bladder cancer is a serious cancer in the world, especially in advanced countries. Bladder cancer stem cells (CSCs) drive bladder tumorigenesis and metastasis. Circular RNAs (circRNAs) are involved in many biological processes, but their roles in bladder oncogenesis and bladder CSCs are unclear. Here, we identified that circGprc5a is upregulated in bladder tumors and CSCs. circGpr5a knockdown impairs the self-renewal and metastasis of bladder CSCs, and its overexpression exerts an opposite role. circGpr5a has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 35 publications
0
63
0
1
Order By: Relevance
“…For example, knockdown of circGprc5a, a circRNA with peptide-coding potential and functions through a peptide-dependent manner, impaired the selfrenewal and metastasis of bladder CSCs. 156 Together, data demonstrated that circRNA may provide a potential biomarker and therapeutic target for the management of bladder cancer.…”
Section: Bladder Cancermentioning
confidence: 95%
“…For example, knockdown of circGprc5a, a circRNA with peptide-coding potential and functions through a peptide-dependent manner, impaired the selfrenewal and metastasis of bladder CSCs. 156 Together, data demonstrated that circRNA may provide a potential biomarker and therapeutic target for the management of bladder cancer.…”
Section: Bladder Cancermentioning
confidence: 95%
“…108 CircGprc5a is upregulated in BC and BC stem cells. 109 In BC stem cells, circGprc5a interacts with peptides and binds to Gprc5a, a key factor in bladder CSCs, in a peptide-dependent manner. 109 Gprc5a is highly expressed in BC stem cells and promotes their self-renewal and metastasis.…”
Section: Regulation Of Tumor Stem Cellsmentioning
confidence: 99%
“…109 In BC stem cells, circGprc5a interacts with peptides and binds to Gprc5a, a key factor in bladder CSCs, in a peptide-dependent manner. 109 Gprc5a is highly expressed in BC stem cells and promotes their self-renewal and metastasis. 109 Expression of hsa_circ_0068307 is upregulated in tumor cell lines, and inhibiting the expression of this circRNA can slow cell invasion and proliferation.…”
Section: Regulation Of Tumor Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies covered a total of 14 circRNAs spread among 1430 patients who were pathologically diagnosed as suffering from BC in Asia. Seven of these circRNAs were associated with poor clinicopathological outcomes (Tang et al, 2017;Zhong et al, 2017;Gu et al, 2018;Huang et al, 2018;Su et al, 2019;Zeng et al, 2019;Zhang et al, 2019c); and the remaining seven were associated with better clinicopathological outcomes (Liu et al, 2018a(Liu et al, , 2018bYang et al, 2018;Bi et al, 2019;Dong et al, 2019;Li et al, 2019a;Yan et al, 2019). In addition, our baseline data also included the miRNA levels reported in the primary studies that are thought to be part of a ceRNA network that regulates the expression of tumor genes.…”
Section: Study Characteristics and Study Qualitymentioning
confidence: 99%